Identification and validation of multiple cell surface markers of clinical-grade adipose-derived mesenchymal stromal cells as novel release criteria for good manufacturing practice-compliant production. Issue 1 (December 2016) - Camilleri, Emily; Gustafson, Michael; Dudakovic, Amel; Riester, Scott; Garces, Catalina; Paradise, Christopher; Takai, Hideki; Karperien, Marcel; Cool, Simon; Sampen, Hee-Jeong; Larson, A.; Qu, Wenchun; et al.
Abstract Background Clinical translation of mesenchymal stromal cells (MSCs) necessitates basic characterization of the cell product since variability in biological source and processing of MSCs may impact therapeutic outcomes. Although expression of classical cell surface markers (e.g., CD90, CD73, CD105, and CD44) is used to define MSCs, identification of functionally relevant cell surface markers would provide more robust release criteria and options for quality control. In addition, cell surface expression may distinguish between MSCs from different sources, including bone marrow-derived MSCs and clinical-grade adipose-derived MSCs (AMSCs) grown in human platelet lysate (hPL). Methods In this work we utilized quantitative PCR, flow cytometry, and RNA-sequencing to characterize AMSCs grown in hPL and validated non-classical markers in 15 clinical-grade donors. Results We characterized the surface marker transcriptome of AMSCs, validated the expression of classical markers, and identified nine non-classical markers (i.e., CD36, CD163, CD271, CD200, CD273, CD274, CD146, CD248, and CD140B) that may potentially discriminate AMSCs from other cell types. More importantly, these markers exhibit variability in cell surface expression among different cell isolates from a diverse cohort of donors, including freshly prepared, previously frozen, or proliferative state AMSCs and may be informative when manufacturing cells. Conclusions Our study establishes that clinical-grade AMSCs expanded in hPL represent a homogeneous cell culture population according to classical markers, . Additionally, we validated new biomarkers for further AMSC characterization that may provide novel information guiding the development of new release criteria. Clinical trials Use of Autologous Bone Marrow Aspirate Concentrate in Painful Knee Osteoarthritis (BMAC): Clinicaltrials.govNCT01931007 . Registered August 26, 2013. MSC for Occlusive Disease of the Kidney: Clinicaltrials.govNCT01840540 . Registered April 23, 2013. Mesenchymal Stem Cell Therapy in Multiple System Atrophy: Clinicaltrials.govNCT02315027 . Registered October 31, 2014. Efficacy and Safety of Adult Human Mesenchymal Stem Cells to Treat Steroid Refractory Acute Graft Versus Host Disease. Clinicaltrials.govNCT00366145 . Registered August 17, 2006. A Dose-escalation Safety Trial for Intrathecal Autologous Mesenchymal Stem Cell Therapy in Amyotrophic Lateral Sclerosis. Clinicaltrials.govNCT01609283 . Registered May 18, 2012.